Analisa Kadar High Density Lipoprotein (HDL) dan Low Density Lipoprotein (LDL) pada Perokok Berat di Rumah Sakit Grandmed Lubuk Pakam - Sari, Sofiani; Tarigan, Emarisa Br.; Sitepu, Rahmadani (Jurnal Inovasi Global, 2025)
Cigarettes are the product of processed tobacco wrapped in cigars or other forms produced by the plants Nicotiana tabacum, Nicotiana rustica and other species or their synthesis containing nicotine and tar with or without additional ingredients. Smoking is a habit in society that is difficult to break and is dangerous for health. Burning cigarettes produces cigarette smoke which is divided into main cigarette smoke and sidestream smoke. Cigarette smoke produced from the inhalation of active smokers contains 25% levels of hazardous substances, while cigarette smoke from burning cigarettes inhaled by passive smokers contains 75% levels of hazardous substances (Nuradi & Jangga, 2020). Based on the background above, this is the formulation The problem is the analysis of HDL and LDL levels in heavy smoking patients? The research population was men and women who were heavy smokers who had HDL and LDL levels checked at Grandmed Lubuk Pakam Hospital as many as 24 people. The research results showed that the majority were male, 20 people ( 83.3%), based on the number of years of smoking, the majority were in the 11-20 year category, 9 people (37.5%), and based on the amount of smoking, the majority were 1-2 packs, 17 people (70.8%). From the results of the analysis of length of smoking with HDL and LDL levels in active smokers, there was an increase in HDL and LDL in the category of length of smoking 11-20 years. -4 Bks in one day's consumption.